Pengaruh Keaktifan Berorganisasi terhadap Indeks Prestasi Mahasiswa Fisika - Hidayah, Yuliani; Jahid , Sarah Mohamad; Setiaji, Bayu (Physical Sciences, Life Science and Engineering, 2023)
Organizational activeness is the involvement of a person to be active in participating in an activity. Most campus communities are of the view that being active in organizations has a negative impact on the Student Achievement Index. The purpose of this study is to determine whether or not there is an influence between organizational activity on student achievement. This research is quantitative research with correlational method. The samples used were 60 students of Physics Education and Physics Education of Yogyakarta State University. The sampling method used is Simple Random sampling. The data collection technique in the study was a questionnaire. The data analysis technique used is the Correlation Test. The result obtained is that there is no influence between organizational activity on the Student Achievement Index. Soo it can be concluded that low or high organizational activity will not affect the Achievement Index obtained. Soo there is nothing wrong if students choose to organize because it will not affect the acquisition of their Achievement Index.